ENVIRONMENTAL ENHANCEMENT INCREASED SPATIAL MEMORY BUT NO SINGNIFICANT EFFECT ON ANXIETY IN RAT WITH PROPYLTHIOURACIL INDUCTION - Noor, Zulkhah; Puspitasari, Dewi Alfika; Adiyani, Oktavia (BRIN - Badan Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of environmental enrichment on spatial memory and anxiety in Propylthiouracil (PTU)-induced thyroid disorder rats. The design of this study was an experimental post test and controlled group design to analyze differences in spatial memory in rats at the end of the study. The subjects in this study were normal rat pups and Rat with PTU induction. Subjects were divided into 4 groups namely, the control group, the normal group with environmental enrichment, the rat group with PTU induction, and the rat group with PTU induction with environmental enrichment. Each group consisted of 8 rats. At the time the rats were born, the rats were given 0.025% PTU which was mixed in their drink and given to the mother until the rats were born until they were 4 weeks old. Environmental enrichment was carried out for 6 weeks. The spatial memory test in Rat was carried out when the pups were 60 days old. Data analysis used One Way Annova, Kruskal Wallis, Post Hoc Test and Mann-Whitney Test. Enrichment of the environment increased the learning latency time of normal rats by 27.8 ± 1.509 seconds to 9.9 ± 4.434 seconds with memory retention increasing by 6.85% (p <0.05). Environmental enrichment in PTU-induced rats accelerated from 84.5 ± 8.70 to 77 ± 1.383 with memory retention increasing by 7.06% (p <0.05). Environmental enrichment did not significantly affect the behavior and anxiety of normal rats or PTU induced (p>0.05). Environmental enrichment to normal rats and impaired thyroid function can increase spatial memory but has no effect on reducing anxiety.